Monotonicity and oscillation for fractional differential equations with Riemann-Liouville derivatives - Bartušek Miroslav; Došlá Zuzana (Demonstratio Mathematica)
Monotonicity, oscillation, and asymptotic behavior of solutions of nonlinear fractional differential equations are investigated. Fractional differential equations are classified according to their oscillation properties, and a comparison between the classical differential operator and the Riemann-Liouville operator is made.